Síntese e caracterização de CaZrO3 e BaZrO3 nanoestruturados - Ibiapino, Amanda Laura (2013)
SYNTHESIS AND CHARACTERIZATION OF NANOSTRUCTURED CaZrO3 AND BaZrO3. In this work, nanostructured samples of barium zirconate (BaZrO3) and calcium zirconate (CaZrO3) were synthesized by the gel-combustion method, using glycine as fuel. The ceramic powders were calcined at 550 °C for 2 h and subsequently heat treated at 1350 °C for 10 min (fast-firing). The X-ray diffraction technique was employed to identify and characterize the crystalline phases present in the synthesized powders, using the Rietveld method. Monophasic nanostructured samples of BaZrO3 and CaZrO3 presenting average crystallite sizes of around 8.5 and 10.3 nm, respectively, were found after fast-firing.